Food Taboos and Cultural Resilience: A Study on the Role of Rice Prohibition in Maintaining Food Security and Ecological Sustainability - Anditasari, Putri; Dilawati, Rika; Ahmadi, Farhan Agung; Hendrawangsyah, Hendrawangsyah (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
This research explores the role of food taboos in Kampung Adat Cireundeu, focusing on the community’s prohibition against rice consumption and its significance in maintaining cultural identity and food security. Using a qualitative descriptive approach, data were collected through in-depth interviews with key informants and direct observations of the community’s food practices. Historical and secondary data were also reviewed. The study found that the food taboos in Cireundeu are deeply connected to the community's historical resistance to colonisation and their religious beliefs in Sunda Wiwitan. These taboos serve as a cultural safeguard and a strategy for ensuring food resilience by relying on cassava as a staple crop. The findings suggest that indigenous knowledge systems and food taboos can play a critical role in promoting sustainable food security and cultural preservation. This has implications for policy development in areas of food sovereignty and ecological sustainability. This research offers a novel perspective on the intersection of historical, cultural, and ecological factors in shaping food practices, contributing to the broader understanding of how food taboos function within indigenous communities to maintain resilience against modern challenges.